2014
DOI: 10.1177/0300060514554724
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and pharmaceutical strategies in steroid-induced osteonecrosis of the femoral head: A literature review

Abstract: The underlying pathology of steroid-induced osteonecrosis of the femoral head (ONFH) is unclear but is known to be multifactorial. It is therefore difficult to find a single predictive biomarker for this disease, and multiple biomarkers are likely to contribute to ONFH progression. Investigation of protein-protein interactions is vital in order to elucidate fully the pathogenesis of this disease, and provide new treatment strategies. This review article discusses the known biomarkers and current treatment stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Although the pathophysiology of NONFH has yet to be fully elucidated, previous studies hypothesize that NONFH is induced by vascular impairment, altered bone cell physiology, oxidative stress, and insufficient blood supply among other factors. [ 1 2 22 23 ] Meanwhile, alcohol intake[ 24 25 26 ] and steroid use[ 10 27 28 29 30 ] have been identified as the major risk factors for NONFH. While this is consistent with our findings, glucocorticoid intake was found to have a stronger association with NONFH than alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathophysiology of NONFH has yet to be fully elucidated, previous studies hypothesize that NONFH is induced by vascular impairment, altered bone cell physiology, oxidative stress, and insufficient blood supply among other factors. [ 1 2 22 23 ] Meanwhile, alcohol intake[ 24 25 26 ] and steroid use[ 10 27 28 29 30 ] have been identified as the major risk factors for NONFH. While this is consistent with our findings, glucocorticoid intake was found to have a stronger association with NONFH than alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…While stem cell factor (SCF)19 and grape seed proanthocyanidin proved protective by reducing oxidative stress20. Based on the studies mentioned above, it is widely suspected that oxidative stress leads to osteonecrosis of ONFH21. Effective, selective, multifunctional drugs suppressing oxidative stress have tremendous potential in ONFH treatment, which can be realized by nanocomposites.…”
mentioning
confidence: 99%
“…A consensus etiopathogenesis of steroid-associated ON has been recently unified on both intravascular thrombosis-induced occlusion and extravascular lipid deposition–induced pressure, leading to impairment of intraosseous blood supply [28] . Therefore, an ideal agent for preventing CS-induced ONFH should simultaneously target both intravascular thrombosis and extravascular lipid deposition [22] . Motomura et al combined anticoagulant and lipid-lowering treatments in animal models and showed that the combined drug group had a significantly lower incidence of osteonecrosis than both the anticoagulant and the lipid-lowering groups (5%, 33% and 38%, respectively) [13] .…”
Section: Discussionmentioning
confidence: 99%
“…As CS impairs osteogenesis of osteoblasts and increases apoptosis of osteoblasts and osteocytes and the adipogenic potential of bone marrow mesenchymal cells, Fufang herbs may share the common pathways or the similar underlying mechanisms for the prevention of both osteoporosis and osteonecrosis [21] . Moreover, around 90% of the patients with CS-induced osteonecrosis coexisted with or accompanied by osteoporosis [22] .…”
Section: Introductionmentioning
confidence: 99%